2012
DOI: 10.1364/oe.20.027102
|View full text |Cite
|
Sign up to set email alerts
|

Generating tunable optical pulses over the ultrabroad range of 16–25 μm in GeO_2-doped silica fibers with an Er:fiber laser source

Abstract: We report generation of femtosecond optical pulses tunable in the 1.6-2.5 μm range using GeO2-doped core silica-cladding fibers. Optical solitons with a duration of 80-160 fs have been measured by the FROG technique in the 2-2.3 μm range. To the best of our knowledge, these are the longest wavelength temporally characterized solitons generated in silica-based fibers. We have also demonstrated more than octave-spanning femtosecond supercontinuum generation in the 1.0-2.6 μm range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 23 publications
3
22
0
1
Order By: Relevance
“…The ZDW of the GeO 2 fibre was estimated at 1808 nm and its group velocity dispersion (GVD) at the pump wavelength (1.95 µm) was -5.41 ps 2 km −1 . This matches the results from a recent report using a similar fibre [Ana12]. Thus, the GeO 2 fibre was pumped in the region of low anomalous GVD and the continuum dynamics were initiated by modulation instability, given the pump format.…”
Section: Supercontinuum Generationsupporting
confidence: 89%
See 1 more Smart Citation
“…The ZDW of the GeO 2 fibre was estimated at 1808 nm and its group velocity dispersion (GVD) at the pump wavelength (1.95 µm) was -5.41 ps 2 km −1 . This matches the results from a recent report using a similar fibre [Ana12]. Thus, the GeO 2 fibre was pumped in the region of low anomalous GVD and the continuum dynamics were initiated by modulation instability, given the pump format.…”
Section: Supercontinuum Generationsupporting
confidence: 89%
“…Some recent progress of Raman-soliton continuum has been made using highly-doped GeO 2 silica-clad fibre pumped with an Er-source [Ana12,Kam12]. The bandwidth of the continuum exceeded 1000 nm, with the long-wavelength limit at 2.5 µm.…”
Section: Overview Of 2-5 µM Supercontinuum Generationmentioning
confidence: 99%
“…A significant asymmetry could be observed in the spectrum, as most of the power resided in 1500 nm to 2600 nm wavelength region. In 2012, Anashkina et al demonstrated a femtosecond SC generation in the 1.0-2.6 μm wavelength range [16]. Optical solitons with duration of 80-160 fs were measured in the 2-2.3 μm wavelength range.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Raman-soliton continuum generation was demonstrated in a highly-doped GeO 2 silica-clad fiber, using an Er-based pump source [24,25]. The bandwidth of the continuum exceeded 1000 nm, with the long-wavelength limit at 2.5 µm [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The bandwidth of the continuum exceeded 1000 nm, with the long-wavelength limit at 2.5 µm [24,25]. Extension of the infrared edge of the continuum can be achieved using a longer wavelength pump source [26,27].…”
Section: Introductionmentioning
confidence: 99%